Genetics and fine mapping of a purple leaf gene, BoPr, in ornamental kale (Brassica oleracea L. var. acephala) - Liu, Xiao-ping (BMC Genomics, 2017)
BACKGROUND: Due to its variegated and colorful leaves, ornamental kale (Brassica oleracea L. var. acephala) has become a popular ornamental plant. In this study, we report the fine mapping and analysis of a candidate purple leaf gene using a backcross population and an F(2) population derived from two parental lines: W1827 (with white leaves) and P1835 (with purple leaves). RESULTS: Genetic analysis indicated that the purple leaf trait is controlled by a single dominant gene, which we named BoPr. Using markers developed based on the reference genome ‘02–12’, the BoPr gene was preliminarily mapped to a 280-kb interval of chromosome C09, with flanking markers M17 and BoID4714 at genetic distances of 4.3 cM and 1.5 cM, respectively. The recombination rate within this interval is almost 12 times higher than the usual level, which could be caused by assembly error for reference genome ‘02–12’ at this interval. Primers were designed based on ‘TO1000’, another B. oleracea reference genome. Among the newly designed InDel markers, BRID485 and BRID490 were found to be the closest to BoPr, flanking the gene at genetic distances of 0.1 cM and 0.2 cM, respectively; the interval between the two markers is 44.8 kb (reference genome ‘TO1000’). Seven annotated genes are located within the 44.8 kb genomic region, of which only Bo9g058630 shows high homology to AT5G42800 (dihydroflavonol reductase), which was identified as a candidate gene for BoPr. Blast analysis revealed that this 44.8 kb interval is located on an unanchored scaffold (Scaffold000035_P2) of ‘02–12’, confirming the existence of assembly error at the interval between M17 and BoID4714 for reference genome ‘02–12’. CONCLUSIONS: This study identified a candidate gene for BoPr and lays a foundation for the cloning and functional analysis of this gene. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12864-017-3613-x) contains supplementary material, which is available to authorized users.